Availability analysis of transmission system using Markov model. (20th May 2009) - Michael, S.; Mariappan, V.; Amonkar, Uday. J.; Telang, A.D.
Technologically advanced transmission system operates economically only if a high rate of availability of the system is achieved. Therefore, it is very important to integrate the analysis of systems reliability and availability into the process of planning and designing the structure of a transmission system. This article discusses the availability modelling and analysis of transmission lines. As the failure phenomenon is stochastic and data analysis reveals negative exponential behaviour, Markov model has been found more appropriate in this study. The study involves live case of Goa Electricity Department. The code written in MATLAB 7.0 for data analysis is used for the Markov model. The Laplace transition matrix involved in stochastic modelling has been solved by using algorithm developed in MATLAB 7.0. Besides, failure interaction physically taking place in the field is also taken into account in the analysis. Component level failure mode effect analysis of extra high voltage transmission lines have also been developed and reported with appropriate results and discussions.